Effectiveness of Applied Behavior Analysis Therapy Against Decreased Distracted Behavior in Children Attention Deficit Hyperactive Disorder - Adela Seftiani; Sri Nugroho Jati; Risna Hayati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Epidemiological data indicate that ADHD (Attention Deficit Hyperactive Disorder) affects the population of children and young adults worldwide by 3.4%. Difficulty in focusing attention is accompanied by an increase in excessive motor activity, one of which is overcome by using the ABA (Applied Behavior Analysis) method of therapy. The purpose of this study is to determine whether ABA therapy reduces distracted behavior in children with ADHD using an experimental design in one participant. Subjects have criteria, namely, children aged 5-6 years and experiencing ADHD problems. This exploration information assortment strategy as perception, meetings, and documentation. The aftereffects of the review expressed that ABA therapy was effective in reducing distracted behavior in children with ADHD. The subject experienced a decrease in distracted behavior withha significance value of 0,043 (p<0,05). Starting from the beginning before being given treatment or the pre-test stage, the frequency of distraction was 112 times, compared to the final stage after being given treatment, the frequency of distraction was 30 times. Data epidemiologi mengindikasikan bahwa ADHD (Attention Deficit Hyperactive Disorder) mempengaruhi populasi anak dan dewasa muda diseluruh dunia sebesar 3,4%. Kesulitan dalam memusatkan perhatian disertai dengan meningkatnya aktivitas motorik yang berlebihan salah satunya diatasi dengan terapi ABA (Applied Behavior Analysis). Tujuan penelitian ialah untuk mengetahui efektivitas terapi ABA terhadap penurunan perilaku terdistraksi pada anak ADHD dengan menggunakan experimental design pada satu partisipan. Subjek memiliki kriteria yaitu, anak berusia 5-6 tahun dan mengalami permasalahan ADHD. Metode pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Hasil penelitian menyatakan bahwa terapi ABA efektif untuk mengurangi perilaku terdistraksi pada anak dengan gangguan ADHD. Subjek mengalami penurunan perilaku terdistraksi dengann nilai signifikansi 0,043 (p<0,05). Terhitung mulai dari awal sebelum diberikan perlakuan atau tahap pre-test frekuensi terdistraksi sebesar 112 kali, dibandingkan dengan tahap akhir setelah diberikan perlakuan frekuensi distraksinya sebanyak 30 kali.